(untitled) (Journal of Human Sciences, 2023)
The book, Turbar Tarabulus (The Road to Tripoli), is a written play which depicts how the Trans Saharan trade between Kano city in Hausaland (Bilad as Sudan) in the present-day Nigeria and Tripoli in Libya, in Arab North Africa (Magreb), has been an avenue for merchants who engaged in a journey for commercial purposes, between 14th and 19th centuries. The journey was undertaken across the Sahara desert on camel or donkey as well as on foot to their destinations. Some researchers tend to ignore the real happenings during the journey, especially the cultural aspects associated with the merchentile activities (e.g. fatauci) and dwell much on the journey; the slave trade and its commercial benefits and its illegality. An analytical, textual and intrinsic study of the play was made to ascertain the types of real activities that were carried out enroute to and from the two cities (Kano and Tripoli) as per what is obtained in the play. The researchers therefore adopted the objectives of ‘realism’ as the modern literary theory that they applied on the play and as a result, their findings showed that during the journey, some real cultural activities like commercial, religious, social, ethnic, medicinal as well as magical (for protection) etc, were carried out in those days.